How Can Facebook Use in Education Be Realized as Crowdsourcing of Learning? an Exploration of Junior, Senior and Graduates Working Together - Varda, Christiana; Ioannou, Andri (My University, 2021)
The popularity of Facebook makes it a particularly interesting platform to explore within an educational setting. In this article, we report on the use of Facebook to support a Media Studies A-level course that involved current and former students using a closed Facebook group. At the time of the study, the group included 106 graduates, and 21 junior and senior students who were the main participants of the study. We employed qualitative content analysis of focus-group and individual interview data to examine how Facebook was realized and used by juniors and seniors brought together to work as a group. Researchers perceived the emerging perceptions of the participants and self-reported interactions to be closely linked to the crowdsourcing model as presented in fields outside education. The study demonstrates how a Facebook group of mixed juniors, seniors and graduates can stimulate collective intelligence; it acts as an aggregator of subject-specific content that is created and disseminated by the online community and builds on a corpus of knowledge that is shared among group members and evolves organically. The work elaborates on a crowdsourcing model of Facebook use in secondary education, and equips practitioners with new knowledge to maximize the educational potential of Facebook with today’s learners.
Keywords: Collaborative learning; Crowdsourcing; Facebook; Secondary education; Technology enhanced learning